Hubungan Komunikasi Interpersonal Antara Pustakawan dan Pemustaka di Perpustakaan SMK Negeri 2 Padang - Ananda, Silvya; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purposes of this study were to (1) describe interpersonal communication relationship between the librarian with user, (2) describe the constraints and solutions obtacles encountered in establishing communication with user at the Library of SMK Negeri 2 Padang. The constraints obtacles encountered in establishing communication with user at the Library of SMK Negeri 2 Padang. Based on analyzing the data, it was concluded. First, at the Library of SMK Negeri 2 Padang between the librarians and users are not intertwined interpersonal communication (interpersonal) as only librarians are trying to communicate to the user. cause the user does not want to communicate the librarian because the librarian was not able to give information that is easily understood by the user. Second, the constraints faced in entablising communication between libraria with user at SMK Negeri 2 Padang is: (1) Interpersonal communication is only one way, (2) users do not reveal information to the librarian, (3) there is a difference of opinion between the user librarians. Third, the face solution constraints in establishing communication is: (1) helping users find the collection, (2) develop the ability to communicate, (3) the dissent evaluate. Keywords: interpersonal communication; interpersonal relationships